Desarrollo morfológico y rendimiento del cultivo de pepino (Cucumis sativus) mediante sistema hidropónico de sustrato sólido en el cantón Babahoyo - Rosado Morán, Milton Emilio (2013)
The present investigation work was carried out in the Ability of Agricultural Sciences of the Technical University of Babahoyo, located in the km. 7 ½ of the road Babahoyo-Montalvo with coordinated geographical of south latitude 79º 32` and latitude west 01º 49´15" with a height of 8 msnm. The area presents a half temperature of 25,6 ºC; humidity relative stocking of 78%, precipitation 1414,19 mm and half speed of the wind of 1,1 m/s. It was used as material genetic cucumber seeds, hybrid Benth Alfha, Diamond F1, Humocaro and variety Market Lives. The treatments were constituted by the cucumber cultivares, subjected to two dose of nutritious solution; being the first dose 2.5 solution cc TO + 1.0 solution cc B and the second dose 7 solution cc TO + 4 solution cc B. the experimental design of Complete Blocks was used at random, with four treatments and four repetitions. All the variables were subjected by means of the test of Multiple Ranges of Duncan to 5% of probability.